Meningkatkan Hasil Belajar Peserta Didik Dengan Menggunakan Metode Tanya Jawab Pada Mata Pelajaran PAI Kelas IV DI UPTD SDN 03 Ampalu - Efnida Efnida; Syawaluddin Syawaluddin; Deslita Deslita; Rio Satria; Restu Mutiara Sari; Puspani Utami Putri (Jurnal Pendidikan Tuntas, 2024)
Education aims to increase the quantity and quality of students. In the learning process, the selection of appropriate learning methods greatly affects the high and low learning outcomes of students. learning methods are ways that educators can make the teaching and learning process run effectively. The problem in this study is the low learning outcomes of students in Islamic Religious Education subjects. because the learning methods used are still not varied. To overcome these problems, researchers applied the Question-and-Answer method with the aim of improving Islamic Education learning outcomes in class IV students of SDN 03 Ampalu. This research uses the type of classroom action research (PTK). The subjects in this study were class IV students of SDN 03 Ampalu totaling 15 students consisting of 7 male students and 8 female students. Classroom action research was carried out in four cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it shows that the average learning outcomes of students have increased. It is known that the KKM value that has been determined from the school is 70. In cycle I, it is known that 8 students have not completed the research with a percentage of 62% and 7 students who have completed it. In cycle II, there was an increase of 9 students who were complete with a percentage of 69% and 6 students who were not complete. Furthermore, in cycle III there was an increase of 11 students with a percentage of 77% and 4 students who were not complete with a percentage. Furthermore, in cycle IV it also increased as many as 14 students reached a complete score with a percentage of 82%, only 1 student who was not complete. Thus, the question and answer method can improve student learning outcomes in PAI subjects at SDN 03 Ampalu.